1995
DOI: 10.1152/ajprenal.1995.268.4.f657
|View full text |Cite
|
Sign up to set email alerts
|

Renal localization and actions of adrenomedullin: a natriuretic peptide

Abstract: Adrenomedullin (ADM) is a newly described 52-amino acid peptide originally isolated from extracts of human pheochromocytoma and, more recently, detected in human plasma. Based on the report that ADM mRNA and immunoreactivity are present in the kidney, the current study was designed to determine the renal distribution of ADM by immunohistochemistry and the renal biological actions of ADM. In the immunohistochemical studies, the present investigation demonstrated the localization of ADM in glomeruli, cortical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
135
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 0 publications
9
135
1
1
Order By: Relevance
“…In addition, AM and PAMP immunoreactivity was also found in proximal convoluted tubules (Fig. 2E) and collecting ducts of some species, in agreement with previous observations (Jougasaki et al, 1995.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, AM and PAMP immunoreactivity was also found in proximal convoluted tubules (Fig. 2E) and collecting ducts of some species, in agreement with previous observations (Jougasaki et al, 1995.…”
Section: Resultssupporting
confidence: 92%
“…AM gene expression and/or AM peptide secretion by mesangial cells (Ichiki et al, , 1995Owada et al, 1995;Shimokubo et al, 1996;Michibata et al, 1998;Chini et al, 1997;Lai et al, 1998) and by renal tubule cell lines (Sato et al, 1998) has been elucidated by indirect methods. In two immunohistochemical studies, performed in paraffin sections, AM immunoreactivity was detected in glomeruli, distal tubules, and medullary collecting ducts of dog kidney (Jougasaki et al, 1995. In addition, Jensen et al (1996Jensen et al ( , 1997 have identified by RT-PCR the presence of AM in afferent and efferent arterioles, but not in juxtaglomerular granular cells in culture.…”
mentioning
confidence: 97%
“…It is synthesized as a 185 amino acid precursor which is processed by consecutive enzymatic steps into a 6000 molecular mass bioactive peptide (Kitamura et al 1993b, Sugo et al 1994. AM production has been characterized in a wide spectrum of tissues, including the cardiovascular (Sakata et al 1993), nervous (Ueta et al 1995, Wang et al 1995, Satoh et al 1996, respiratory (Martínez et al 1995b), endocrine , Satoh et al 1996, renal (Jougaski et al 1994), and digestive systems (Washimine et al 1995). AM mRNA expression is enhanced by inflammatory response elements (interleukin-1 and tumor necrosis factor) and the peptide is markedly up-regulated in the circulation following endotoxin (lipopolysaccharide) challenge or bacterial sepsis (Sugo et al 1995, Hirata et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…1 AM is primarily secreted by vascular cells, and it is also secreted from kidney, lung, and heart. 2 AM functions as a local autocrine/paracrine mediator, 3 as well as a circulating hormone, 4 exerting natriuretic, 5 antioxidative, 6,7 and other effects. AM levels in the blood are increased in hypertension, 4,8 heart failure, 9 and myocardial infarction, 10 which suggests its involvement in cardiovascular disease.…”
mentioning
confidence: 99%